1999
DOI: 10.1007/s000110050440
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of elastase-induced acute inflammation and pulmonary emphysema in hamsters by a novel neutrophil elastase inhibitor FR901277

Abstract: These results suggest that FR901277 inhibits the elastase activity potently both in vitro and in vivo, and that elastase may play a role at least in part in pathogenesis of pulmonary emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…NE-I significantly inhibits elastase-induced paw edema in mice at 10 mg/kg with a median effective dose (ED 50 ) for inhibiting elastase-induced lung hemorrhage and pulmonary emphysema of about 8 mg/kg. 44 In preliminary studies, we observed 57% to 78% inhibition of NE in plasma and marrow between 1 and 8 hours after administration of G-CSF, and 78% to 85% inhibition of marrow NE on day 5, after 4 days of dosing with NE-I and our standard 4-day G-CSFmobilizing regimen. This dose of NE-I has also been shown to block CFU-GM mobilization and SDF-1 degradation in marrow in G-CSFmobilized mice.…”
Section: In Vivo Mmp-9 and Ne Neutralizationmentioning
confidence: 72%
“…NE-I significantly inhibits elastase-induced paw edema in mice at 10 mg/kg with a median effective dose (ED 50 ) for inhibiting elastase-induced lung hemorrhage and pulmonary emphysema of about 8 mg/kg. 44 In preliminary studies, we observed 57% to 78% inhibition of NE in plasma and marrow between 1 and 8 hours after administration of G-CSF, and 78% to 85% inhibition of marrow NE on day 5, after 4 days of dosing with NE-I and our standard 4-day G-CSFmobilizing regimen. This dose of NE-I has also been shown to block CFU-GM mobilization and SDF-1 degradation in marrow in G-CSFmobilized mice.…”
Section: In Vivo Mmp-9 and Ne Neutralizationmentioning
confidence: 72%
“…An alternative approach is to develop small molecule inhibitors of neutrophil elastase [266] and ONO-5046 and FR901277 have high potency [267]. These drugs inhibit neutrophil elastase-induced lung injury in experimental animals, whether given by inhalation or systemically and also inhibit the other serine proteinases released from neutrophils, namely cathepsin G and proteinase-3, that may mediate features of COPD.…”
Section: Neutrophil Elastase Inhibitorsmentioning
confidence: 99%
“…Elastolytic activity of carotid arteries (n ϭ 25) was assessed by Elastin-Congo red degradation assay as previously described 22,32 with some modification. For acidic protease activity of cathepsins, 21 100 g of total protein from each sample was incubated with 1 mg/ml ElastinCongo red containing 0.05% Triton X-100, 20 mmol/L sodium acetate, and 1 mmol/L EDTA, pH 5.5; for a study of MMP activity, the same amounts of total proteins were added to 1 mg/ml Elastin-Congo red and incubated in 10 mmol/L phosphate, pH 7.2, containing 150 mmol/L NaCl, 1% Triton-100, 15 mmol/L CaCl 2 , 0.1% SDS, 0.5% Na deoxycholate, and 0.2% Na azide.…”
Section: Elastase Assaymentioning
confidence: 99%